Vapor Phase Polymerization Deposition Conducting Polymer Nanocomposites on Porous Dielectric Surface as High Performance Electrode Materials - Yang, Yajie; Zhang, Luning; Li, Shibin; Wang, Zhiming; Xu, Jianhua; Yang, Wenyao; Jiang, Yadong (Nano-Micro Letters, 2013)
We report chemical vapor phase polymerization (VPP) deposition of poly(3,4-ethylenedioxythiophene) (PEDOT) and PEDOT/graphene on porous dielectric tantalum pentoxide (Ta2O5) surface as cathode films for solid tantalum electrolyte capacitors. The modified oxidant/oxidant-graphene films were first deposited on Ta2O5 by dip-coating, and VPP process was subsequently utilized to transfer oxidant/oxidant-graphene into PEDOT/PEDOT-graphene films. The SEM images showed PEDOT/PEDOT-graphene films was successfully constructed on porous Ta2O5 surface through VPP deposition, and a solid tantalum electrolyte capacitor with conducting polymer-graphene nano-composites as cathode films was constructed. The high conductivity nature of PEDOT-graphene leads to resistance decrease of cathode films and lower contact resistance between PEDOT/graphene and carbon paste. This nano-composite cathode films based capacitor showed ultralow equivalent series resistance (ESR) ca. 12Ω and exhibited excellent capacitance-frequency performance, which can keep 82% of initial capacitance at 500 KHz. The investigation on leakage current revealed that the device encapsulation process has no influence on capacitor leakage current, indicating the excellent mechanical strength of PEDOT/PEDOT-gaphene films. This high conductivity and mechanical strength of graphene-based polymer films shows promising future for electrode materials such as capacitors, organic solar cells and electrochemical energy storage devices.